History Matters for Organizations: An Integrative Framework for Understanding Influences from the Past - Marquis, Christopher; Qiao, Kunyuan (Academy of Management Review, 2025)
We develop a comprehensive framework of how history matters for organizations. We first decompose the past into two distinct stages: (a) junctures and (b) processual periods. “Junctures” are relatively short periods when organizations develop structures, routines, and cultures that then have a lasting influence. “Processual periods” are longer and more stable times when past influence may become strengthened, preserved, or weakened. Combining one juncture and one processual period, we develop a typology of six ideal types of historical influence encompassing cohort effect, imprinting, path dependence, inertial decay, path stability, and dissipation. Our integrative framework helps (a) advance existing and extend new theories of the past, (b) enable empirical research on historical processes to draw more convincing conclusions from data, and (c) better inform the practice of managing influences from the past. Our study sets the stage for more cumulative knowledge of how history enduringly matters for organizations.